2010
DOI: 10.1007/s10212-010-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Negative expertise: comparing differently tenured elder care nurses' negative knowledge

Abstract: Negative expertise is conceptualised as the professional's ability to avoid errors during practice due to certain cognitive agencies. In this study, negative knowledge (i.e. knowledge about what is wrong in a certain context and situation) is conceptualised as one such agency. This study compares and investigates the negative knowledge of elder care nurses at three different levels of professional experience. Thereby, various forms of negative knowledge-declarative, procedural, self-reflective and vicarious-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Heimbeck et al, 2003;Ingold, 2001;Keith, 2012). This adds to prior studies (Gartmeier et al, 2008;Gartmeier et al, 2011;Hetzner et al, 2012;Oser et al, 2012) having emphasized how learning from errors results in the development of negative knowledge and certainty in persons' work methods and procedures. Instead, the current study suggests that students and teachers share reflections of how what are judged to be proper procedures are negotiable and changeable in relation to the task context, rather than being fixed and stable.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Heimbeck et al, 2003;Ingold, 2001;Keith, 2012). This adds to prior studies (Gartmeier et al, 2008;Gartmeier et al, 2011;Hetzner et al, 2012;Oser et al, 2012) having emphasized how learning from errors results in the development of negative knowledge and certainty in persons' work methods and procedures. Instead, the current study suggests that students and teachers share reflections of how what are judged to be proper procedures are negotiable and changeable in relation to the task context, rather than being fixed and stable.…”
Section: Discussionmentioning
confidence: 60%
“…In particular, prior research has been concerned with how persons are given opportunities to participate in and experience the making of errors (Dalehefte et al, 2012;Gartmeier et al, 2008;Heimbeck et al, 2003;Keith, 2012). For example, in a study of care nurses, it was found that their experienced knowledge about various workplace errors was important for their ability to actively avoid errors in their work (Gartmeier, Lehtinen, Gruber, & Heid, 2011). This implies that the active experiencing of errors is important for persons' learning of how to improve their practices.…”
Section: Interactional Processes Related To Experiencing Errorsmentioning
confidence: 99%
See 2 more Smart Citations